Optimization of Way Rarem Reservoir Operation with Dynamic Program - Adhi Putra, Ginanjar; Dermawan, Very (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2026)
Way Rarem Reservoir, located in North Lampung Regency, Lampung Province, is a multipurpose reservoir that supplies water for 15,080 hectares of irrigation area and provides flood control for the downstream region. For more than 30 years of operation, the Way Rarem reservoir has followed a conventional operating policy, which is now irrelevant given current conditions. An improvement in the performance of the Rarem reservoir is required. This study aims to improve reservoir performance by optimizing the reservoir operation policy. This study applied a deterministic dynamic program to optimize the reservoir operation policy using CSUDP and compared its performance with the existing operation. The optimization model can increase reliability by 2.93%. The optimization model also showed a higher resiliency value (3.08) than the existing operation (0.49) and a lower Tfail value (4.54) than the existing one (4.67). The optimization model showed a lower total deficit (629.22 MCM) than the existing (698.69 MCM) for vulnerability. It also has a smaller average deficit (1.95 MCM) than the existing (8.32) for every failure state. However, the optimization model showed a larger maximum deficit (34.55 MCM) than the existing (22.11 MCM).